Metabolic constraints of swelling‐activated glutamate release in astrocytes and their implication for ischemic tissue damage. Issue 2 (18th June 2019) - Wilson, Corinne S.; Bach, Martin D.; Ashkavand, Zahra; Norman, Kenneth R.; Martino, Nina; Adam, Alejandro P.; Mongin, Alexander A.
Abstract : In stroke, pathological cell swelling promotes ischemic brain damage via activation of the glutamate‐permeable, volume‐regulated anion channel (VRAC). As VRAC activity requires cytosolic ATP, we explored in rat astrocyte cultures whether metabolic inhibition limits or prevents VRAC‐mediated glutamate release, which was traced with a radiolabeled glutamate analog. Our findings suggest that in the ischemic penumbra, astrocytic VRAC activity can be fully sustained by glycolysis even when glucose and oxygen levels are dramatically reduced. Open Science: This manuscript was awarded with the Open Materials Badge For more information see: https://cos.io/our-services/open-science-badges/ Abstract: Volume‐regulated anion channel (VRAC) is a glutamate‐permeable channel that is activated by physiological and pathological cell swelling and promotes ischemic brain damage. However, because VRAC opening requires cytosolic ATP, it is not clear if and how its activity is sustained in the metabolically compromised CNS. In the present study, we used cultured astrocytes – the cell type which shows prominent swelling in stroke – to model how metabolic stress and changes in gene expression may impact VRAC function in the ischemic and post‐ischemic brain. The metabolic state of primary rat astrocytes was modified with chemical inhibitors and examined using luciferin–luciferase ATP assays and a Seahorse analyzer. Swelling‐activated glutamate release was quantified with the radiotracer D‐[ 3 H]aspartate. The specific contribution of VRAC to swelling‐activated glutamate efflux was validated by RNAi knockdown of the essential subunit, leucine‐rich repeat‐containing 8A (LRRC8A); expression levels of VRAC components were measured with qRT‐PCR. Using this methodology, we found that complete metabolic inhibition with the glycolysis blocker 2‐deoxy‐D‐glucose and the mitochondrial poison sodium cyanide reduced astrocytic ATP levels by > 90% and abolished glutamate release from swollen cells (via VRAC). When only mitochondrial respiration was inhibited by cyanide or rotenone, the intracellular ATP levels and VRAC activity were largely preserved. Bypassing glycolysis by providing the mitochondrial substrates pyruvate and/or glutamine led to partial recovery of ATP levels and VRAC activity. Unexpectedly, the metabolic block of VRAC was overridden when ATP‐depleted cells were exposed to extreme cell swelling (≥ 50% reduction in medium osmolarity). Twenty‐four hour anoxic adaptation caused a moderate reduction in the expression levels of the VRAC component LRRC8A, but no significant changes in VRAC activity. Overall, our findings suggest that (i) astrocytic VRAC activity and metabolism can be sustained by low levels of glucose and (ii) the inhibitory influence of diminishing ATP levels and the stimulatory effect of cellular swelling are the two major factors that govern VRAC activity in the ischemic brain.